como se resuelve 2x-(x+1)/4=5x+2/6
Respuestas a la pregunta
Contestado por
6
▪RESPUESTA▪
-1
▪EXPLICACIÓN PASO A PASO▪
\begin{gathered}\frac{2x-(x+1)}{4} =\frac{5x+2}{6} \\\\\frac{2x-x-1}{4} =\frac{5x+2}{6} \\\\\frac{x-1}{4} =\frac{5x+2}{6} \\\\6(x-1)=4(5x+2)\\6x-6=20x+8\\-14=14x\\-1=x\end{gathered}
4
2x−(x+1)
=
6
5x+2
4
2x−x−1
=
6
5x+2
4
x−1
=
6
5x+2
6(x−1)=4(5x+2)
6x−6=20x+8
−14=14x
−1=x
▪ESPERO TE AYUDE :)
▪ME PUEDES SEGUIR XFIS?
jhojantorresrodrigue:
no entendí
Otras preguntas
Matemáticas,
hace 5 meses
Castellano,
hace 5 meses
Historia,
hace 5 meses
Matemáticas,
hace 9 meses
Castellano,
hace 9 meses
Educ. Fisica,
hace 1 año
Arte,
hace 1 año
Ciencias Sociales,
hace 1 año